Indoor Fungal Load in Broiler Flocks Environment at Different Stages of Production Cycle - Ahmed , Marwa F.E.; Khalifa, Marwa I.; El-Wahab, Amr Abd; Youssef, Mohamed A.A. (International Journal of Poultry Science, 2016)
A longitudinal study was developed in order to determine the fungal contamination level (mould and yeast) in air, settled dust and litter of three broiler flocks at different stages of production cycle at 10 day fixed interval. Air samples were obtained from the examined flocks using impingement and the environmental pooled samples were collected from settled dust and litter. The concentrations of mould and yeast colonies count in air, settled dust and litter in a broiler flocks have been found to rise with bird age reaching maximum at end of production cycle. The most predominant genera of mould were among Aspergillius, Penicillium, Mucor and Alternaria spp. while, Cryptococcus, Geotricum and Candida spp. were the dominant yeast genus. The examined samples contained group two risk species of Aspergillius fumigatus and Candida albicans. The high contamination of broiler facilities with fungi in summer season indicating importance of proper biosecurity measures and good ventilation. Furthermore, presence of pathogenic fungi may provoke adverse effects for animal and workers health beside the surrounding environment.